HPLC Method for Determination of p-coumaric acid from the Medicinal Herb Leptadinia reticulata - N. P. Geetha; M. Mahesh; B. K. Bettadaiah; R. K. Kini; H. S. Prakash (International Journal of Phytomedicine, 2011)
The aim of present study was to develop and validate a simple, precise and rapid HPLC method for the quantification of p-coumaric acid in Leptadinia reticulata extractst. The analysis was performed by reverse-phase chromatography on an phenomenex C18 columns with isocratic elution of Methanol and 0.8%-Formic acid in water (6:4) at a flow rate of 1.0mL/min, a column temperature of 35°C, photodiode array detector detection at 326 nm. The method validated in terms of linearity accuracy precision LOD, LOQ and stability. The herb Leptidinia reticulata contains 0.17% p-coumaric acid. The linear range of method was 0.25-50µg/ml with correlation coefficient of 0.9993, the recovery was 98-99.4% and the relative standard deviation is 0.98 % (n=6). The developed method was found to be a relatively simple, precise and reproducible for the quantification of p-coumaric acid. The method does not employ any derivatization procedure and can be used as a quality control tool for the routine analysis of p-coumaric acid from an herb Leptadinia reticulata.